Estimation of Age and gender Among Yemeni Population using 3D craniometry: A Computed Tomography based study - Saddam M. Al-zofi; Caroline Edward Ayad; Fahd Naji Thawaba; Abdullah Taher Naji (International Organization of Scientific Research (IOSR), 2021)
Aim: This study aimed to estimate age and gender for Yemeni population through the cranium measurements using three dimensional Computed Tomography ((3D CT). Materials and Methods: This cross sectional study was done in the Radiology department of University of Science and Technology Hospital, Sanaa City-Yemen .362 patients were included (190 were males and 172 were females) with different ages. All were examined using CT scan for the cranium. Axial scan was obtained, then 3D reconstruction volume rendering technique (VRT) performed to take cranial measurements for foramen magnum length and width, Bizygomatic breadth and Basion-prosthion length using RadiAnt DICOM Viewer version 5. The measurements were compared according to age and gender. Results: The mean and standard deviation of all cranial measurements were higher in males than female, and the cranial measurements increased with age from infancy to later adulthood with statistical significant difference between both genders and between different age groups (p<0.05). Conclusion: The human cranium considered as a reliable parameter in age and gender determination for forensic and anthropology using 3D Computed Tomography.